Hubungan Dukungan Organisasi dengan Komitmen Kerja pada Personil Korps Brimob Polda Sumatera Utara - Ndruru, Bernad Ekarisman (Psikologi Prima, 2024)
Organizational Support is a social, emotional, thought, and behavioral process in an individual's relationship with the organization, where individuals can adapt to the challenges and difficulties. This study aims to look at the relationship between organizational Support and the work commitment of Poldasu Brimob Corps personnel. This research uses quantitative methods. The population in this study amounted to 777 people. The research sample used a random sampling technique with 125 personnel. The measuring instruments used are the organizational Support and work commitment scales. Simple linear regression analysis is a technique used in this study. The results showed a significant relationship between organizational Support and work commitment with the coefficient Freg = 24.657; sig <0.00. This result makes the hypothesis acceptable. There is a significant relationship between organizational Support and work commitment, with a correlation coefficient rx₂y=0.488; sig<0.001, with a practical contribution weight of 29%. That is, 71% influence or other factors influence work commitment. The subjects in this study had high organizational Support and high work commitment. On that basis, the Brimob Corps personnel are expected to continue improving the existing organizational Support to maintain maximum work commitment.